Only the largest terrestrial carnivores increase their dietary breadth with increasing prey richness. (3rd June 2020) - Ferretti, Francesco; Lovari, Sandro; Lucherini, Mauro; Hayward, Matt; Stephens, Philip A.
Abstract: Animals should adapt their foraging habits, changing their dietary breadth in response to variation in the richness and availability of food resources. Understanding how species modify their dietary breadth according to variation in resource richness would support predictions of their responses to environmental changes that alter prey communities. We evaluated relationships between the dietary breadth of large terrestrial carnivores and the local richness of large prey (defined as the number of species). We tested alternative predictions suggested by ecological and evolutionary theories: with increasing prey richness, species would (1) show a more diverse diet, thus broadening their dietary breadth, or (2) narrow their dietary breadth, indicating specialisation on a smaller number of prey. We collated data from 505 studies of the diets of 12 species of large terrestrial mammalian carnivores to model relationships between two indices of dietary breadth and local prey richness. For the majority of species, we found no evidence for narrowing dietary breadth (i.e. increased specialisation) with increasing prey richness. Although the snow leopard and the dhole appeared to use a lower number of large prey species with increasing prey richness, larger sample sizes are needed to support this result. With increasing prey richness, the five largest carnivores (puma Puma concolor, spotted hyaena Crocuta crocuta, jaguar Panthera onca, lion Panthera leo, and tiger Panthera tigris ), plus the Eurasian lynx Lynx lynx and the grey wolf Canis lupus (which are usually top predators in the areas from which data were obtained), showed greater dietary breadth and/or used a greater number of large prey species (i.e. increased generalism). We suggest that dominant large carnivores encounter little competition in expanding their dietary breadth with increasing prey richness; conversely, the dietary niche of subordinate large carnivores is limited by competition with larger, dominant predators. We suggest that, over evolutionary time, resource partitioning is more important in shaping the dietary niche of smaller, inferior competitors than the niche of dominant ones. Abstract : Predators may change their diets according to prey availability. We evaluated the dietary breadth of large terrestrial carnivores and the local richness of large prey (number of species), to test alternative predictions: with increasing prey richness, species (1) show a more diverse diet, broadening their dietary breadth, or (2) narrow their dietary breadth, specialising on a smaller number of prey. For most species, we found no evidence for increased specialisation with increasing prey richness. The five largest carnivores (tiger, lion, jaguar, spotted hyaena, and puma), the grey wolf and the Eurasian lynx (top predators), showed greater dietary breadth (increased generalism). Results suggest that large carnivores encounter little competition in expanding their dietary breadth with increasing prey richness, but the diet of subordinate large carnivores is limited by competition with larger, dominant predators. Over evolutionary time, resource partitioning should be more important in shaping the dietary niche of smaller, inferior competitors than that of dominant ones.